Evaluation of coronary artery side branches (SB) with Quantitative Flow Ratio (QFR) by comparing the use of recommended angiographic projections with routine angiographic projections as Reference. (3rd October 2022) - Antoniadis, M; Blum, M; Ussat, M; Laufs, U; Lenk, K
Abstract: Background: Contrast-flow quantitative flow ratio (QFR) is a novel, noninvasive method for the quantitative evaluation of coronary physiology using computational fluid dynamics based on 3D vessel reconstruction in angiograms. Computing this 3D-model with analyzing the dynamics of the contrast medium flow with a specialized algorithm, the software computes the virtual FFR. This new technique has shown a high accuracy in determining the functional significance of coronary stenosis of the three main epicardial coronary arteries using the gold standard FFR as reference. However, QFR data for the evaluation of coronary side branches (SB) are scarce. Therefore, the study aimed to determine the feasibility of this novel method to analyze SB and to characterize optimal viewing angles for evaluation using QFR. Methods: A total of 87 patients, who underwent invasive coronary angiography with routine core lab projections, were enrolled in the study and were analyzed retrospectively by two certified experts with the software QAngio XA 3D 3.2. In addition, 37 patients were enrolled prospectively using coronary angiography projections recommended for the virtual QFR-Analysis. Quantitative Analysis was performed only for SB with a maximum lumen diameter (MLD) of ≥2mm. The following outcome parameters were analyzed: baseline characteristics, anatomical SB parameters such as MLD (mm) and vessel length (VL; mm) of the SB, result of the QFR-computation and procedure parameters, such as use of applicated contrast medium and fluoroscopy time. Results: 187 side branches (obtuse marginal [OM], diagonal branch [DB], intermediate artery [IA], posterolateral branch [PLB] and posterior descending artery [PDA]) were analyzed using QFR. Out of 87 patients undergoing an invasive coronary angiography with routine core lab projections with 244 SB ≥2mm, 123 SB (55%) were computable with the use of QFR. In the prospective cohort of 37 patients with recommended angiographic projections for QFR analysis of main branches, 75 SB ≥2mm were found. 64 of the 75 SB (84%) were computable with the use of QFR. The use of recommended projections led to an overall higher evaluability of SB (85% vs. 55%). The data show that the fluoroscopy time for recommended QFR projections was not significantly different as the time for routine cath lab projections (3.7±2.2 vs. 4.6±3, p=2.69). The study shows a significant increase of the amount of contrast medium used for QFR projections (55.4±24.2 vs. 87.9±43.7, p<0.01). Conclusion: To our knowledge this is the first study evaluating QFR for SB analysis. QFR is feasible for the routine assessment of side branches (SD) with MLD ≥2mm. The use of recommended projections significantly improved the quality of the QFR SB analysis apart from PDA, without increasing the fluoroscopy time during coronary angiography. Overall QFR could increase the use of physiologically guided coronary interventions, not only for the main epicardial vessels, but also for the SB. Funding Acknowledgement: Type of funding sources: None.